2022
DOI: 10.1111/liv.15497
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term hepatic safety of lomitapide in homozygous familial hypercholesterolaemia

Abstract: Introduction: Lomitapide is a microsomal triglyceride transfer protein inhibitor for patients with homozygous familial hypercholesterolaemia. Due to its mechanism of action, potential hepatic effects of lomitapide are of clinical interest. This study aimed to determine the long-term hepatic safety of lomitapide. Methods: Data were aggregated from the pivotal phase 3 and extension phase clinical trial with lomitapide (median 5.1 years; serum total bilirubin, transaminases, cytokeratin-18 [CK-18] and enhanced li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The data analysis showed that lomitapide has been associated with temporary elevations in liver transaminases, both alanine aminotransferase (ALT) and aspartate aminotransferase (AST), with no occurrences of increases in bilirubin levels, a moderate buildup of fat in the liver, and elevations in hepatic biomarkers and hepatic stiffness. However, the analysis did not show the clinical impact of lomitapide treatment on liver damage during the long-term study [106].…”
Section: Lomitapidementioning
confidence: 84%
“…The data analysis showed that lomitapide has been associated with temporary elevations in liver transaminases, both alanine aminotransferase (ALT) and aspartate aminotransferase (AST), with no occurrences of increases in bilirubin levels, a moderate buildup of fat in the liver, and elevations in hepatic biomarkers and hepatic stiffness. However, the analysis did not show the clinical impact of lomitapide treatment on liver damage during the long-term study [106].…”
Section: Lomitapidementioning
confidence: 84%
“…It is a microsomal triglyceride transfer protein (MTP) inhibitor that decreases the formation of very low density lipid chylomicrons and reduces LDL-C levels 84 . Adverse effects are primarily gastrointestinal events, with rare cases of hepatic injury being reported 85 , 86 . Evidence of its long-term safety and efficacy for HoFH patients in European and Japanese studies has been published, although more extensive phase 3 trials are still required 87 89 .…”
Section: Methodsmentioning
confidence: 99%
“…The median dose used was 40 mg, however, it has been shown to achieve equivalent LDL-C lowering effects or greater at lower doses [77] . Although lomitapide is linked to an increase in hepatic steatosis, a study aiming to explore the long-term hepatic safety of lomitapide found no clinically significant elevations in hepatic biomarkers, and hepatic stiffness remained normal for over 9-years of follow-up [78] .…”
Section: Additional Ldl-c Lowering Therapies For Homozygous Familial ...mentioning
confidence: 99%